Applications and Challenges for the Use of Phosphatidylethanol Testing in Liver Disease Patients (Mini Review). (28th December 2017) - Nguyen, Van Long; Haber, Paul S.; Seth, Devanshi
Abstract : Phosphatidylethanol (PEth) is a direct nonoxidative metabolite of ethanol that may be measured in clinical samples as a marker for monitoring alcohol consumption. It has been used in a wide variety of clinical and nonclinical settings; however, its investigation in relation to liver disease has been limited. This study aims at providing a short review on the applications and challenges for the incorporation of PEth testing in identifying alcohol intake in this patient population. Abstract : Proposed hypothetical model of enhanced PEth formation in advanced liver disease. As liver disease progresses, the enzymatic activity of alcohol dehydrogenase and aldehyde dehydrogenase is decreased [1]. As a consequence oxidative metabolism of ethanol may be impaired yielding higher blood ethanol levels being shunted towards non‐oxidative PEth pathway via phospholipase D (PLD) [2]. PLD has a greater affinity for ethanol than its usual substrate phosphatidylcholine [3], suggesting the possibility of intrinsic PEth formation in erythrocytes [4].